2020
DOI: 10.1111/eff.12545
|View full text |Cite
|
Sign up to set email alerts
|

Migration and escapement of silver eel males, Anguilla anguilla, from a southwestern European river

Abstract: The catadromous life cycle of the European eel encompasses a spawning migration to the Sargasso Sea. Prior to their migration, eels develop a silver coloration being referred to as “silver eels.” Due to the dramatic European eel recruitment decline, it is crucial to quantify silver eel escapement to evaluate the success of measures taken under Eel Management Plans (Regulation EC (1100/2007)). Thus, the percentage of silver eels escaping from the River Mondego (Portugal) was estimated during two consecutive spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 56 publications
(105 reference statements)
0
6
0
Order By: Relevance
“…High summer discharge events have recently been more frequent and discharge variations may have stimulated a progressive early trigger of the migration on the Burrishoole River over the study period as observed by Sandlund et al 18 , who have also proposed that this shift might be induced by a change in spring conditions leading to earlier silvering. In contrast, in the Mediterranean region, warm water temperatures combined with low discharges prevented silver eels from migrating during summer/fall and delayed migration until a water temperature drop in December/ January 50 , several months later than in northern latitudes 16 . The contrasting trends in environmental conditions induced by global climate change is a real challenge for a panmictic species whose evolutionary capacities for local adaptation are limited 51 .…”
Section: Discussionmentioning
confidence: 95%
“…High summer discharge events have recently been more frequent and discharge variations may have stimulated a progressive early trigger of the migration on the Burrishoole River over the study period as observed by Sandlund et al 18 , who have also proposed that this shift might be induced by a change in spring conditions leading to earlier silvering. In contrast, in the Mediterranean region, warm water temperatures combined with low discharges prevented silver eels from migrating during summer/fall and delayed migration until a water temperature drop in December/ January 50 , several months later than in northern latitudes 16 . The contrasting trends in environmental conditions induced by global climate change is a real challenge for a panmictic species whose evolutionary capacities for local adaptation are limited 51 .…”
Section: Discussionmentioning
confidence: 95%
“…Beside the specimens from November that have the lowest nutrition, the specimens from April also have lower values compared to other periods. As it is known, and already mentioned above, that European eels migrate to the sea during late autumn and early winter for spawning (Dekker et al 1998;Davidsen et al 2011;Monteiro et al 2020), it can be assumed that those that are better fed in that period already migrated, and those who are less fed remained, so CF is therefore significantly different from those from the period of March, June and August. Condition factor compares the wellbeing of a fish and is based on the hypothesis that heavier fish of a given length are in better condition (Bagenal & Tesch 1978).…”
Section: Discussionmentioning
confidence: 99%
“…River fractals indicate the complexity of river morphology and affect the space of eels that can freely move and predation, further affecting the spatial distribution of eels (Wiley et al ., 2004). Recent research revealed that water conductivity is the most influential predictor affecting silver eel migration (Monteiro et al ., 2020). Our results show that conductivity has little effect on juveniles and young eels.…”
Section: Discussionmentioning
confidence: 99%